LEARNING OUTCOMES OF PHYSICAL EDUCATION FOR ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL - Asep Hasbullah; Achmad Sofyan Hanif; Yasep Setiakarnawijaya; Ramdan Pelana (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to analyze and determine the effect of physical activity, learning environment, and learning motivation on physical education, sport. This study used quantitative approach with a descriptive method. This research was conducted at Senior High School 1 Cikarang Timur with a sample of 90 students of eleventh grade through simple random sampling technique. The data analysis technique used is path analysis. The results of this study indicate that (1) there is a positive direct effect of physical activity on physical education learning outcomes with a calculation of 0.258, (2) there is a positive direct influence of the learning environment on physical education learning outcomes with a calculation of 0.212, (3) there is a positive direct effect of learning motivation on physical education learning outcomes with a calculation of 0.288, (4) there is a direct positive effect of physical activity on learning motivation with a calculation of 0.325, and (5) there is a direct positive effect of the learning environment on learning motivation with a calculation of 0.334. Thus, the conclusion shows that physical activity, learning environment, and learning motivation are important factors to improve learning outcomes at Senior High School 1 Cikarang Timur.